Microstructure and electrical properties of perovskite (Pb, La)TiO3 thin film deposited at low temperature by the polymeric precursor method - Pontes, F. M.; Rangel, JHG; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Araujo, E. B.; Eiras, J. A. (Kluwer Academic Publ, 2001)
High-quality (Pb, La)TiO3 ferroelectric thin films were successfully prepared on a Pt(111)/Ti/SiO2/Si(100) substrate for the first time by spin coating, using the polymeric precursor method. The X-ray diffraction patterns show that the films are polycrystalline in nature. This method allows for low temperature (500 degrees C) synthesis, a high quality microstructure and superior dielectric properties. The effects on the microstructure and electrical properties were studied by changing the La content. The films annealed at 500 degreesC have a single perovskite phase with only a tetragonal or pseudocubic structure. As the La content is increased, the dielectric constant of PLT thin films increases from 570 up to 1138 at room temperature. The C-V and P-E characteristics of perovskite thin films prepared at a low temperature show normal ferroelectric behavior, representing the ferroelectric switching property. The remanent polarization and coercive field of the films deposited decreased due to the transformation from the ferroelectric to the paraelectric phase with an increased La content. (C) 2001 Kluwer Academic Publishers.